Comparison of the Antiemetic Effects of Metoclopramide and Dexamethasone in Women Undergoing Cesarean Section Under Spinal Anesthesia - Ibrahim, Mohanad Ghazi; Hussein, Israa AbdAli (Journal of Neonatal Surgery, 2025)
It is well known that the most common problems faced by patients who receive spinal anesthesia for cesarean section (C/S) are nausea and vomiting. It turns out that 8 mg of intravenous (IV) dexamethasone versus 10 mg of intravenous metoclopramide has potent action to reduce the incidence of these two troubles. Additionally, changes in vital signs were checked in the present study. The categories of our study were chosen based on ASA I and II classifications, with ages ranging from 18 to 40 years old with a BMI between 18 and 25. The total number of pregnant patients was 80. The patients were randomly classified into either Group M (n=40) receiving 8 mg of IV dexamethasone or Group N (n=40) obtaining 10 mg of metoclopramide intravenously. Following 8 mg of dexamethasone or 10 mg of metoclopramide, heart rate, SPO2%, arterial arterial pressure, and the frequency of nausea or vomiting were recorded at 1, 5, 10, 15, 30, and 60 minutes for all categories of both groups. For spinal anesthesia, 12.5 mg of bupivacaine 0.5% was administered intrathecally for both groups. After complete monitoring and checking, the findings suggest that age, BMI, and SPO2 were non-significantly changed due to the selection of dexamethasone or metoclopramide. However, the impacts of these antiemetics on patients' hemodynamics and nausea and vomiting were significantly influenced after administration of spinal anesthetic. The study concluded that dexamethasone and metoclopramide, during cesarean delivery, revealed significant differences in the frequency of nausea and vomiting, heart rate, and arterial blood pressure between the two groups. Metoclopramide showed the lowest baseline mean frequency of nausea and vomiting at all time points, while dexamethasone represented the highest baseline mean for mean arterial pressure (MAP) and pulse rate (PR) according to the monitoring time points selected. In order to maximize patient outcomes following cesarean birth, healthcare providers should carefully take these considerations into account while choosing medications.